Attitudes of Secondary School Students toward Health Promotion Behaviors in Al- Hila City - Hasaan Abd Ali1 , Salma K . Jihad2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives To identify the school students sociodemographic characteristics . To assess the attitude of participants toward health promotion . Methodology: A cross-sectional descriptive study consisting of (177)students ,to Attitudes of Secondary School Students toward Health Promotion Behaviors of secondary school student in Al- Hilla City Result: :Analysis of data reveals that there is a( 67.8%) of adolescent have a normal body mass index, and (15.8) have underweight, (12.4%) overweight, while(4%) only have obesity. Conclusion: Most of the students maintained normal weight status according to their BMI. Most of students aged at middle adolescence period, males more than females, majority of students were un married, at fourth grade, most of them were urban residence and ordered as 2nd member in the family, majority of them were not smoking and live with their parents.